2014
DOI: 10.7763/ijmo.2014.v4.347
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Alternative Fuel Combustion in a Rotary Cement Kiln Burner

Abstract: Abstract-Increased use of alternative fuels in cement kilns is a trend in the world. However, replacing fossil fuels like coal with different alternative fuels will give various impacts on the overall kiln process due to the inherent fuel characteristics. Hence, it is important to know to what extent the fossil fuels can be replaced by different alternative fuels without severely changing process conditions, product quality or emissions. In the present study, a mathematical model based on a mass and energy bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…, Ariyaratne et al. ), the multidimensional representation (tables , , and appendices A and B in the supporting information available on the Journal's website), without being case specific, enables simultaneous consideration of any number and type of AFs and decouples the impact of AF composition and feed‐rate uncertainty. It allows peer comparative assessment of various AF scenaria under the same kiln/precalciner/preheater conditions (e.g., temperature).…”
Section: Assessment Of Industrial Waste Alternative Fuel Valorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…, Ariyaratne et al. ), the multidimensional representation (tables , , and appendices A and B in the supporting information available on the Journal's website), without being case specific, enables simultaneous consideration of any number and type of AFs and decouples the impact of AF composition and feed‐rate uncertainty. It allows peer comparative assessment of various AF scenaria under the same kiln/precalciner/preheater conditions (e.g., temperature).…”
Section: Assessment Of Industrial Waste Alternative Fuel Valorizationmentioning
confidence: 99%
“…The enthalpy balance, hardly considered in LCI assessments, and variations in flue gas and stack (offgas) volumes and composition play a key role in plant operability (Tsiliyannis ; Ariyaratne et al. ) and emissions compliance, often under stricter limits than baseline. Capacity constraints and operability are also rarely considered in life cycle assessment (LCA) studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinker production involves burning limestone at high temperatures, which requires a significant amount of fuel [7,8]. This process leads to carbon emissions not only from the calcination reaction but also from the fuel combustion reaction in the kiln [9,10]. To address his issue, cement producers have been making efforts to reduce clinker by using alternative materials such as trass, slag, fly ash, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This is a pure biofuel and hence more attractive as an environmentally friendly fuel. In a previous modeling study carried out by the authors of the current study, it was found that the kiln gas flow rate is higher and the kiln gas temperature is lower for MBM than for several other solid waste-derived fuels, when replacing 100% of the coal energy in the cement rotary kiln [3], [8]. A full-scale cement kiln test also demonstrated the negative effects of burning high amounts of MBM [9].…”
Section: Introductionmentioning
confidence: 99%
“…This fuel is prepared by grinding and sterilizing slaughter house wastes [8]. This is a pure biofuel and hence more attractive as an environmentally friendly fuel.…”
Section: Introductionmentioning
confidence: 99%